Comparative efficacy and safety of adalimumab biosimilar (BCD-057) and innovator in patients with psoriasis vulgaris. Results of the BCD-057-2/CALYPSO phase III international, multicenter, randomized double-blind clinical trial - Т. V. Korotaeva; A. V. Samtsov; A. L. Bakulev; M. M. Kokhan; I. K. Minullin; O. A. Vylegzhanina; V. V. Dubensky; B. V. Khalilov; A. A. Khotko; O. S. Zykova; I. V. Chumachenko; A. M. Lukyanov; et al. (Современная ревматология, 2018)
The paper gives the results of the phase III clinical trial of adalimumab (ADA) biosimilar, (BCD-057) (BIOCAD, Russia), which demonstrate the clinical equivalence of the biosimilar to the ADA innovator Humira® in patients with moderate and severe psoriasis.Objective. The BCD-057-2/CALYPSO phase III international, multicenter, randomized double-blind clinical trial of the efficacy and safety of BCD-057 (International Nonproprietary Name (INN): adalimumab, ZAO «BIOCARD», Russia) versus Himura® (INN: adalimumab (OOO «Abbvie») in patients with plaque psoriasis aims to prove the equivalent pharmacokinetics, efficacy, safety, and immunogenicity of these medicines in both direct parallel comparison and subsequent switching from innovator to biosimilar.Patients and methods. The investigation enrolled 346 adult patients diagnosed with moderate to severe plaque psoriasis lasting at least 6 months. After screening, the patients were randomized in a 1:1 ratio into BCD-057 or Humira® groups. At week 24, the patients taking Humira® were re-randomized 1:1 into a group to continue treatment with the ADA innovator or into that to switch to BCD-057. The primary efficacy endpoint was to estimate the proportion of patients who had achieved a 75% improvement in Psoriasis Area and Severity Index (PASI75) at week 16. The secondary endpoints included the assessment of the time course of changes in the skin, nails, degree of itching, and quality of life at weeks 16 and 24. Safety was evaluated from the incidence of treatment-associated adverse events (AEs), cases of severe toxicity (grades 3–4 AEs according to the Common Terminology Criteria Adverse Event (CTCAE) 4.03), cases of early patient withdrawal due to AEs, as well as cases of toxicity potentially associated with the use of tumor necrosis factor-α inhibitors. Immunogenicity was determined using the validated test of patient serum samples for binding antibodies (BAb) and neutralizing antibodies.Results and discussion. The per-protocol population for efficacy evaluation included 342 patients. At week 16, the primary endpoint of PASI75 was shown to be achieved by 62.5% (105/168) and 66.46% (109/164) of the patients in the BCD-057 and Himura® groups, respectively; p=0.45). The difference between the groups in PASI75 responses was 3.22% with 95% confidence interval [-14.25%; 6.32%]. The analysis of additional endpoints revealed no significant differences in the efficacy of the biosimilar and innovator. During 24 weeks of the investigation, treatment-associated AEs were recorded in 31.03 and 25.58% of the patients in the BCD-057 and Humira® groups, respectively (p=0.31). The proportion of patients with BAb detected at 16 weeks of the investigation was 25.44 and 24.07% in the BCD-057 and Humira® groups, respectively (p=0.87).Conclusion. The investigation provided convincing clinical evidence for of the equivalent efficacy, safety, and immunogenicity of BCD-057 and Humira®.